Por uma política da libertação do movimento negro no Brasil - Thales Brandão Machado Moreira (2021)
This dissertation follows the trajectory of the brazilian black moviment during the three phases or impulses: from the republican period until the constitution of 19/8788, seeking to indicate approximations with Enrique Dussel’s “Politics of Liberation”. For this, at first, the main characteristics and strategies of the black movement during the indicated period, are pointed out. In a second moment, the political thought of Enrique Dussel is presented using the abstract categories of “Architectonic” and the paths for a political transformation through the second part of the Twenty theses on politics. Finally, the trajectory of the black movement is approached with the “Politics of Liberation” and points of contact are indicated that should serve as an example for new struggles of the social movement in Brazil.